Impact of biologic and targeted synthetic therapies on bone health in immune-mediated inflammatory diseases: a narrative review - Isabel de la Cámara-Fernández; Tatiana Cobo-Ibáñez; Olga María Reillo-Sánchez; Gabriela Nataly Cueva-Nájera; Ana Valeria Acosta-Alfaro; Santiago Muñoz-Fernández (Frontiers in Medicine, 2026)
Background Osteoporosis is a systemic skeletal disorder characterized by reduced bone mass, impaired microarchitecture, and increased fracture risk. Patients with immune-mediated inflammatory diseases (IMIDs) have a higher prevalence of osteoporosis owing to chronic inflammation, glucocorticoid use, and disease-specific factors. Pro-inflammatory cytokines such as TNF- α , IL-1, IL-6, and IL-17 contribute to bone loss, suggesting that therapies targeting these pathways may influence skeletal health. Objective This narrative review aims to evaluate the effects of biological disease-modifying anti-rheumatic drugs (bDMARDs) and targeted synthetic DMARDs (tsDMARDs) on bone metabolism and fracture risk in adults with IMIDs. Methods A comprehensive literature search was conducted in Ovid Medline, Embase, and the Cochrane Central Register of Controlled Trials from 2015 to August 2025, using MeSH and free-text terms. Reference lists of included studies were manually screened. Search strategies were validated by an expert librarian. Results bDMARDs and tsDMARDs, including TNF- α inhibitors, IL-6 inhibitors, abatacept, rituximab, IL-17 inhibitors, and JAK inhibitors, generally preserve or modestly increase bone mineral density (BMD) and favorably modulate bone turnover markers (BTMs), although these effects do not always correlate with changes in BMD. However, in some cases, a decrease in BMD has been reported; this is usually associated with persistent inflammatory disease activity. Despite these effects, evidence for fracture risk reduction is limited and inconsistent, with outcomes influenced by disease activity, structural damage, and classic risk factors. Conclusion bDMARDs and tsDMARDs appear to preserve or modestly improve bone mass and positively influence bone turnover in IMIDs. However, increased BMD does not consistently translate into lower fracture risk, and current evidence is insufficient to draw definitive conclusions regarding the effect of bDMARDs and tsDMARDs on fracture risk.